2013
DOI: 10.1111/jpn.12076
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of α‐linolenic acid to long‐chain omega‐3 fatty acid derivatives and alterations of HDL density subfractions and plasma lipids with dietary polyunsaturated fatty acids in Monk parrots (Myiopsitta monachus)

Abstract: The effect of α-linolenic acid from a flaxseed (FLX)-enriched diet on plasma lipid and fatty acid metabolism and possible atherosclerosis risk factors was studied in Monk parrots (Myiopsitta monachus). Twenty-four Monk parrots were randomly assigned to diets containing either 10% ground SUNs or 10% ground FLXs. Feed intake was calculated daily. Blood samples, body condition scores and body weights were obtained at -5 weeks, day 0, 7, 14, 28, 42 and 70. Plasma samples were analysed for total cholesterol, free c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
1
9
2
Order By: Relevance
“…Later, this technique was used to analyze lipoprotein profiles in dogs, 10 as well as other species. 32,33 In the present study, electron microscopic examination showed that feline lipoproteins were spherical and the diameters of the majority of lipoproteins that fell into the LDL density range were larger than those that fell into the HDL density range as has also been reported in humans and dogs. 34,35 In addition, feline lipoproteins in this study were smaller in diameter than what has previously been reported for lipoproteins in humans and dogs.…”
Section: Discussionsupporting
confidence: 83%
“…Later, this technique was used to analyze lipoprotein profiles in dogs, 10 as well as other species. 32,33 In the present study, electron microscopic examination showed that feline lipoproteins were spherical and the diameters of the majority of lipoproteins that fell into the LDL density range were larger than those that fell into the HDL density range as has also been reported in humans and dogs. 34,35 In addition, feline lipoproteins in this study were smaller in diameter than what has previously been reported for lipoproteins in humans and dogs.…”
Section: Discussionsupporting
confidence: 83%
“…Portomicrons first target the liver, unlike chylomicrons, which first target extra‐hepatic tissues 6 . Lipoprotein subtypes have also been identified in birds, but are poorly characterized in terms of relative abundance, composition, and clinical value 7,8 . Avian apolipoproteins also differ from mammals, and birds lack apoE and apoB‐48.…”
Section: Introductionmentioning
confidence: 99%
“…This technique is extremely time‐consuming, requiring 6‐30 hours of very high‐speed centrifugation with specialized equipment 16 . It is not offered commercially for animals, but has been used for research in pigeons, chickens, quails, geese, Quaker parrots, and cockatiels 6‐9,17‐20 . While this method allows separation and isolation of lipoprotein classes and subclasses, it does not allow the determination of lipoprotein particle numbers and sizes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations